2017
DOI: 10.1103/physrevb.96.094509
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between critical current and flux-flow resistivity in the mixed state of Ba(Fe1xCox)2As2

Abstract: We studied the temperature and magnetic field dependence of vortex dissipation and critical current in the mixed-state of unconventional superconducting alloys Ba(Fe1−xCox)2As2 (0.044 ≤ x ≤ 0.100) through current-voltage measurements. Our results reveal that all the electric field E vs current density j curves in the Ohmic regime merge to one point (j0, E0) and that there is a simple relationship between the critical current density jc and flux-flow resistivity ρ ff : ρ ff /ρn = (1 − jc/j0) −1 , where ρn = E0/… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…11 For x = 0.06, it is suggested that superconductivity coexists with a spin density wave (SDW). 12 For thin films of Ba(Fe 1−x Co x ) 2 As 2 , the exponent n in the temperature dependence of the resistivity is minimum namely, close to unity at x ≈ 0.05 and x ≈ 0.07 for MgO and CaF 2 substrate, respectively, which may be associated with an antiferromagnetic QCP. 13 Furthermore, a sign change in the electronic-magnetic Gruneisen parameter is observed for x = 0.055 and x = 0.065, consistent with the expected behavior at a QCP.…”
Section: A Introductionmentioning
confidence: 91%
“…11 For x = 0.06, it is suggested that superconductivity coexists with a spin density wave (SDW). 12 For thin films of Ba(Fe 1−x Co x ) 2 As 2 , the exponent n in the temperature dependence of the resistivity is minimum namely, close to unity at x ≈ 0.05 and x ≈ 0.07 for MgO and CaF 2 substrate, respectively, which may be associated with an antiferromagnetic QCP. 13 Furthermore, a sign change in the electronic-magnetic Gruneisen parameter is observed for x = 0.055 and x = 0.065, consistent with the expected behavior at a QCP.…”
Section: A Introductionmentioning
confidence: 91%